PERANAN MOTIVASI DALAM MENINGKATKAN PEMAHAMAN STATISTIK - Rosmita Sari Siregar (JURNAL MATHEMATIC PAEDAGOGIC, 2022)
This study aims to determine the role of motivation by looking at the effect of emotional intelligence, lecturers' teaching style and learning media facilities on statistical understanding. The sample in this study was 239 respondents who were students majoring in Accounting at Prima Indonesia University. The data is processed using path analysis. Emotional intelligence, teaching style of lecturers and learning media facilities strongly support motivation to be better. In learning the teaching style of the lecturer is very supportive in growing student motivation, if the lecturer as the main actor in learning has good pedagogical abilities and uses effective learning media in teaching, it will be able to grow student learning motivation and will produce a high level of understanding in the subject. . Students who have good emotional intelligence will have good behavior and motivation in learning. Therefore, the influence of motivation can be seen from emotional intelligence, lecturer's teaching style and learning media facilities in understanding statistics.